KYUDOJO. PLACES FOR PRACTICE KYUDO (Physical Culture and Sport: Scientific Perspective, 2023)
The article reveals the varieties, common functional elements and characteristics of models of Kyudo training halls and their prevalence in the world and in Japan. The relevance of the study is to establish the structure of the hall and to adopt the experience of other countries for the possible further use of this information in the construction or adaptation of the place for kyudo classes.The purpose of the work is to establish the features of the general model of a traditional training hall with kyudo kyudojo.                Results and conclusions. For Kyudo training, you need to have a specialized place (hall) for shooting. It has been established that such a place is kyudojo, one of the types of training hall from modern Japanese martial arts - dojo. The main characteristic feature of these halls is the traditional Japanese style of architecture, the use of certain materials, the location of the hall, etc. The main differences between kyudojo include the following: the range of fire, the structure of the hall and the purpose of the room. Halls are divided into two types, kintekijo and entekijo (short and long distance, respectively). According to the structure of the hall, we can divide it into traditional (or standard) kyudojo, makiwara kyudojo, and kyudojo with one target. According to their purpose, we divided them into those that were built specifically for Kyudo training, and those that were adapted (for example, school playgrounds).                The general model of the structure of the room, which can be conditionally divided into the following components: the main room (or often called the shooting range) syajo, the yaimichi and the place where the matobe targets are placed.                The syajo includes the following elements – kamiza, kamidana, shinpanseki, irigushi, shai (imaginary line), honza, hikai, shimoza, makiwarashitsu, a place to store arrows and bows, a changing room, a coaching room, and a restroom. Matobe is a special indoor room where targets are placed. Its composition includes: adzushimaku, adzusi, kantekisyo. Yamichi with the following elements of yatorimitsi, kankyakuseki, yayoke and yamichi themselves. Yatorimitchi is the only element that can be covered with a canopy or a roof.                It has been established that various types of kyudojo exist wherever kyudo is practiced. Most of them are adapted premises, usually school grounds or dojos of other martial arts. Traditional kyudojo exists on the territory of Japan, France, Romania, USA, Italy, Spain, etc.
Keywords: kyudo; kyudojo; national sport; traditions; ethnosport